Gangguan Pemrosesan Bahasa Akibat Trauma Emosional pada Tokoh Tari dalam Film Bolehkah Sekali Saja Aku Menangis - Bariah Bariah; Dhea Azkia Shalehah; Muhammad Sugianor; Nazwa Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2025)
Language processing disorders are disorders that arise when someone is under mental stress or experiencing deep emotional trauma. This study aims to analyze the various types of language processing disorders experienced by the character Tari in the film